Effectiveness of intraoral splints in the treatment of migraine and tension‐type headache: A systematic review - Olga Martínez‐Álvarez; Eduardo Wojtovicz; Jose Luís De la Hoz; Juan Mesa; Susan Armijo‐Olivo (Wiley, 2023)
Abstract Objectives The main objective of this systematic review was to assess the effectiveness of intraoral splints in treating migraine and tension‐type headaches. Material and Methods The article search was conducted within seven electronic databases (Medline, PubMed, Embase, CINAHL PLUS with full text, Cochrane Library Trials, Web of Science, and Scopus) with no date limits or language restrictions up to June 12, 2022. Strict inclusion and exclusion criteria were set for article selection. At the same time as data extraction, each study's risk of bias (RoB) was evaluated using the Cochrane tool to assess their RoB. Subsequently, the Cochrane Grading of Recommendations Assessment Development and Evaluation was used to evaluate the certainty of the evidence. Results Four controlled clinical trials were included. These trials were heterogeneous in terms of (1) diagnosis, (2) design of the intraoral splints, and (3) tools for reporting the results, which made it difficult to compile the data as well as evaluate its quality. Trials reported a reduction in the frequency of headache and pain intensity when using intraoral splints; however, this therapy was not superior to medications. Conclusions The evidence is very low for the use of oral splints as a therapeutic alternative to medication in the treatment of migraine and/or tension‐type headache.